Estimating site costs prior to conducting clinical trials. (March 2014) - Arenz, Dorothee; Hero, Barbara; Eichhorst, Barbara F; Langer, Martin; Pester, Lars; von Tresckow, Julia; Vehreschild, Jörg J; Vehreschild, Maria JGT; Cornely, Oliver A
Conducting clinical trials is costly and time consuming. Trial sites usually do not calculate site costs. Underestimating required resources slows enrollment and lowers data quality but it is currently unclear how to reliably estimate trial site costs. A group of trial staff designed and validated a tool for compiling trial tasks and calculating required expenditures prior to initiating a clinical trial. The tool was validated in two steps. Round-robin tests for accuracy compared case payments for the same trial calculated by different participants. A narrow CI was reached (22.95–715.69) demonstrating significantly similar estimates of the test participants (p = 0.039). To confirm the predictive value, the predicted and actual hours were compared and a correlation coefficient of 0.952 (p = 0.003) was found. A web-based tool, the Study Site Budgeting Tool, was developed, which allows trial sites to estimate staff costs at the site and determine the budget needed to conduct a clinical trial.